2013
DOI: 10.1038/cddis.2013.322
|View full text |Cite
|
Sign up to set email alerts
|

Interdigital cell death in the embryonic limb is associated with depletion of Reelin in the extracellular matrix

Abstract: Interdigital cell death is a physiological regression process responsible for sculpturing the digits in the embryonic vertebrate limb. Changes in the intensity of this degenerative process account for the different patterns of interdigital webbing among vertebrate species. Here, we show that Reelin is present in the extracellular matrix of the interdigital mesoderm of chick and mouse embryos during the developmental stages of digit formation. Reelin is a large extracellular glycoprotein which has important fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…In all these cases, the embryonic webbing is retained in these species and represents a form of adaptive syndactyly where adjacent digits are joined by interdigital epithelium and mesenchyme, which is typically lost through apoptosis at later stages of embryonic development once digits and phalanges have been patterned (Zuzarte‐Luis and Hurle, ; Zeller et al., ; Hernandez‐Martinez and Covarrubias, ). Fgf8 is generally utilized as a survival factor (retained on axis of the digits) and Bmp signaling is a proapoptotic signal present in the interdigits (Diaz‐Mendoza et al., ; Diaz and Trainor, ). Inhibiting interdigital Bmp signaling in a “webbing free” species like a chicken hindlimb through the introduction of a dominant negative Bmp receptor led to a retention of embryonic interdigital mesenchyme reminiscent of the duck foot and bat hand, for which the latter species inhibit Bmp signaling through heterotopic expression of the Bmp antagonist gremlin in the interdigital mesenchyme (Zou and Niswander, ; Weatherbee et al., ).…”
Section: Developmental and Genetic Work As Case Studiesmentioning
confidence: 99%
“…In all these cases, the embryonic webbing is retained in these species and represents a form of adaptive syndactyly where adjacent digits are joined by interdigital epithelium and mesenchyme, which is typically lost through apoptosis at later stages of embryonic development once digits and phalanges have been patterned (Zuzarte‐Luis and Hurle, ; Zeller et al., ; Hernandez‐Martinez and Covarrubias, ). Fgf8 is generally utilized as a survival factor (retained on axis of the digits) and Bmp signaling is a proapoptotic signal present in the interdigits (Diaz‐Mendoza et al., ; Diaz and Trainor, ). Inhibiting interdigital Bmp signaling in a “webbing free” species like a chicken hindlimb through the introduction of a dominant negative Bmp receptor led to a retention of embryonic interdigital mesenchyme reminiscent of the duck foot and bat hand, for which the latter species inhibit Bmp signaling through heterotopic expression of the Bmp antagonist gremlin in the interdigital mesenchyme (Zou and Niswander, ; Weatherbee et al., ).…”
Section: Developmental and Genetic Work As Case Studiesmentioning
confidence: 99%
“…In a previous study, we have shown that integrin‐mediated Reelin signaling is a survival factor for the undifferentiated interdigital mesoderm (Díaz‐Mendoza et al, ). In this study, cell death evaluated by flow‐cytometry was not intensified in cultures subjected to knock down of either ApoER2 or VLDLR (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 93%
“…However, an increasing number of studies in recent years have provided evidence for a wider distribution of Reelin in the extracellular matrices of tumors and non‐nervous embryonic and adult organs (Maurin et al, ; Sato et al, Khialeeva et al, ; Lutter et al, ; Yuan et al, ; Garcia‐Miranda et al, ). Recognized functions of Reelin unrelated to neural functions include the following: morphogenesis of the lymphatic vessels (Lutter et al, ) inhibition of metastasis in various carcinomas (see Yuan et al, ) homeostasis of the intestinal epithelium (Garcia‐Miranda et al, ) mammary gland morphogenesis (Khialeeva et al, ) and interdigital cell death (Díaz‐Mendoza et al, ). There is also evidence for a greater complexity of the signaling cascade and various transmembrane receptors such as Ephrin B receptor (Bouche et al, ), integrins (Dulabon et al, ), and Amyloid Precursor Protein (Hoe et al, ) appear to be functionally associated with this signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is likely that this miRNA was involved in the changes in the extracellular matrix occurring in the course of interdigit remodelling associated with the onset of interdigit regression (Diaz‐Mendoza et al. ). Notably, miR‐30 targets important components of the interdigit such as CTGF, Snail and Tgfβ2 (Roy et al.…”
Section: Resultsmentioning
confidence: 99%